Saliva Diagnostics in Spaceflight Virology Studies—A Review - Douglass M. Diak; Brian E. Crucian; Mayra Nelman-Gonzalez; Satish K. Mehta (Viruses)
Many biological markers of normal and disease states can be detected in saliva. The benefits of saliva collection for research include being non-invasive, ease of frequent sample collection, saving time, and being cost-effective. A small volume (≈1 mL) of saliva is enough for these analyses that can be collected in just a few minutes. For “dry” saliva paper matrices, additional drying times (about 30 min) may be needed, but this can be performed at room temperature without the need for freezers and specialized equipment. Together, these make saliva an ideal choice of body fluid for many clinical studies from diagnosis to monitoring measurable biological substances in hospital settings, remote, and other general locations including disaster areas. For these reasons, we have been using saliva (dry as well as wet) from astronauts participating in short- and long-duration space missions for over two decades to conduct viral, stress, and immunological studies. We have also extended the use of saliva to space analogs including bed rest, Antarctica, and closed-chamber studies. Saliva is a biomarker-rich and easily accessible body fluid that could enable larger and faster public health screenings, earlier disease detection, and improved patient outcomes. This review summarizes our lessons learned from utilizing saliva in spaceflight research and highlights the advantages and disadvantages of saliva in clinical diagnostics.